Analisis Perbandingan Routing Static Dengan Penerapan IPV4 Dan IPV6 Pada SMPN 9 Kaur - A.R Walad Mahfuzhi; RG Guntur Alam; Agung Karisma Hidayah; Ravi Putra Lingga (Jurnal Media Infotama, 2025)
With the rapid development of internet technology, the need for efficient and stable protocols is increasingly important. This study aims to compare the performance of static routing on IPv4 and IPv6 protocols at SMPN 9 Kaur, with a focus on quality of service (QoS) based on the TIPHON standard. The research method used is the Network Development Life Cycle (NDLC), including the stages of analysis, design, testing, implementation, monitoring, and management. The results show that IPv6 has better performance than IPv4. On an IPv6 network using WiFi, a packet loss of 0%, a delay of 0.43 ms, a jitter of 0.201 ms, and a throughput of 4840 kbps was obtained. Meanwhile, IPv4 based on WiFi had a packet loss of 0%, a delay of 22.1175 ms, a jitter of 7.8903 ms, and a throughput of 409 kbps. The conclusion of this study is that IPv6 is superior in terms of network stability and efficiency compared to IPv4